Use of ECT in Major Vascular Neurocognitive Disorder with Treatment-Resistant Behavioral Disturbance following an Acute Stroke in a Young Patient - Kyle E. Rodenbach; Daniel Varon; Timothey Denko; Ryan Peterson; Carmen Andreescu (Case Reports in Psychiatry)
The following case describes the utilization of bitemporal ECT as a treatment of last resort in a 47-year-old woman with profoundly treatment-resistant behavioral disturbance poststroke. The use of ECT led to improvement in symptoms sufficient for discharge from an inpatient psychiatric unit to the nursing home. Neuropsychiatric sequelae of stroke include poststroke depression, anxiety, mania, psychosis, apathy, pathological laughter and crying, catastrophic reaction, and mild and major vascular neurocognitive disorders. Behavioral disturbance is common and may pose diagnostic and therapeutic difficulty in the poststroke patient. In most cases, first-line treatment includes pharmacologic intervention tailored to the most likely underlying syndrome. Frequent use of sedating medications is a more drastic option when behaviors prove recalcitrant to first-line approaches and markedly affect quality of life and patient safety. ECT is generally safe, is well tolerated, and may be effective in improving symptoms in treatment-resistant behavioral disturbance secondary to stroke with major neurocognitive impairment, as suggested in this case.